USAHA PRODUKSI KERAJINAN SAPU BERBAHAN SERABUT KELAPA BERBASIS WILAYAH - Saputra, Didin Hadi; Widyaningrum, Meiyanti; Bahri, Samsul (International Journal of Community Service Learning, 2018)
The joint business of coconut fiber broom made by Namira and Bina Taruna is a business that has been run by the partner in Telaga Waru Village, Pringgabaya District, East Lombok regency. The effort has been carried out for generations by local villagers. The focus of this activity is on how to oversee the whole business management process, and to administer, document the results of coconut fiber production through marketing media in order to output or the end result (such as increased production and wider market network) to be obtained more optimally and effectively. This Community Partnership Program activity aims to improve the quality of coconut fiber broom products located in Telaga Waru Village, Pringgabaya District, East Lombok regency. Methods of implementation of the PKM offered by the proposing team to the partners of Namira and Bina Taruna include coordination of partner group existence, preparation of schedule of activities, assistance of skill development of partner business group, marketing through assistance, organizing scheduled open house products and facilitating coverage in the print media. The results of this dedication have been felt by the whole community of Telaga Waru village and its surroundings after the participants follow the socialization process and the science is given through direct practice and interactive dialogue process so that from the training result, there will be improvement of understanding before and after training.